2012
DOI: 10.1016/j.jacc.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Pre-procedural Risk Quantification for Carotid Stenting Using the CAS Score

Abstract: The NCDR CAS score, comprising 6 clinical variables, predicts in-hospital S/D after CAS. This tool may be useful to assist clinicians in evaluating optimal management, share more accurate pre-procedural risks with patients, and improve patient selection for CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…Symptomatic status and older age are the 2 most clearly risk factors for CAS in experts’ experience [18] and from Medicare data. [12] Similar to a previous report that symptomatic status is a risk factor for mortality in hospital stroke, [10] we also found a higher frequency of short-term stroke, mortality, and long-term events in symptomatic patients. Congestive heart failure was also observed to affect CAS outcome in a German registry study [19] as well as in a previous efficacy and safety study in Taiwan.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Symptomatic status and older age are the 2 most clearly risk factors for CAS in experts’ experience [18] and from Medicare data. [12] Similar to a previous report that symptomatic status is a risk factor for mortality in hospital stroke, [10] we also found a higher frequency of short-term stroke, mortality, and long-term events in symptomatic patients. Congestive heart failure was also observed to affect CAS outcome in a German registry study [19] as well as in a previous efficacy and safety study in Taiwan.…”
Section: Discussionsupporting
confidence: 89%
“…We developed a nomogram to predict the probability of MACE after CAS based on clinical information from a population-based database. Although older age and lesion-related factors influence the short-term risk of patients undergoing CAS, [10,11] we found that age and comorbidities may be important for long-term outcomes. On the basis of a statistical selection, age was the most important influence risk factor revealed in this nomogram.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, this subset analysis failed to assess aortic arch anatomy as a potential confounding variable. This is a commonality in case series reporting an increased incidence of perioperative stroke events in patients aged 80 years and older,1 3–7 19 with the exception of three studies,9 13 20 all of which found a positive correlation between unfavorable arch anatomy and ischemic complications.…”
Section: Discussionmentioning
confidence: 94%
“…27 Although claims data lack the clinical detail of data sources such as the CAS registry, claims data nevertheless have been previously used successfully to compare risk-standardized outcomes for patients with acute myocardial infarction and acute heart failure. Because hospitals have greater ability to select their CAS recipients than to select the patients who are hospitalized with acute myocardial infarction/acute heart failure, it is possible that unobserved confounders may excessively influence a hospital's RSMR after CAS.…”
Section: Limitationsmentioning
confidence: 99%